Physical and electrochemical study of platinum thin films deposited by sputtering and electrochemical methods (2011)
In this work platinum thin films deposited by sputtering and electrochemicalmethods were characterized through physical and electrochemical analysis. The as-grown platinum thin films were characterized through X-ray diffraction (XRD), atomic force microscopy (AFM); scanning electronic microscopy (SEM) and through electrochemical impedance spectroscopy (EIS) measurements. Structural studies indicated that platinum thin films were polycrystalline. Morphological characteristics were significantly affected by the substrate type and synthesis method. Finally the EIS analysis indicated that platinum films were electrochemically stable and present both low resistance of charge transfer and low series resistance; the equivalent circuit of platinum interface has been proposed.